Factors Associated with The Incidence of Primary Dysmenorrhea in Adolescent Girls - Tria Qorita, Elsa; Atik Maryanti, Syska; Gumiarti (Universitas Bondowoso, 2024)
Background: Background: Dysmenorrhea is severe pain in the lower abdomen during menstruation. The impact on adolescent girls includes pain felt in the abdomen and back. Based on data from the Jember Regency Health Office, 69.5% mostly experienced primary dysmenorrhea. Based on the results of preliminary studies at Senior High School 2 Jember conducted by researchers on 15 young women, 9 young women (60%) experienced dysmenorrhea. This study aims to determine the Factors Associated with the Incidence of Primary Dysmenorrhea in Class X Adolescent Girls at Senior High School 2nd Jember. Methods: This study used descriptive research design. The population in this study were all grade X adolescent girls at Senior High School 2nd Jember who experienced primary dysmenorrhea. The sample amounted to 147 respondents. Research sampling using total sampling technique. The research instrument used was a questionnaire. Data were analyzed using univariate analysis. Results: The frequency distribution of respondents who experienced primary dysmenorrhea based on the age factor of early menarche 61.9%, abnormal menstrual duration 63.3%, there was a family history of dysmenorrhea 61.2%, and abnormal BMI 69.4%. Conclusion: The conclusion in this research is that almost all respondents experience primary dysmenorrhea. Factors associated with the incidence of dysmenorrhea in class X adolescent girls at Senior High School 2 Jember are age of menarche, length of menstruation, family history of dysmenorrhea and Body Mass Index (BMI). Adolescent girls in class X at Senior High School 2nd Jember are advised to manage a healthy lifestyle and exercise regularly.